The Global-Local Strategy For Lumajang Batik Smes: Synergy Of Adaptive Innovation Rooted In Local Wisdom And Diaspora Networks For Business Internationalization - Sumiati Sumiati; Sudarmiatin; Heri Pratikto (International Journal of Business and Quality Research, 2026)
This study aims to examine glocalization strategies among Micro, Small, and Medium Enterprises (MSMEs) in the Batik Lumajang sector through the integration of adaptive innovation and the empowerment of diaspora networks. Amid increasingly intense global competition, MSME actors are required to adopt a global mindset to adapt to a dynamic cross-border business environment (Kossowska & Rosinski, 2020). Using a qualitative approach, this study analyzes how local cultural identity, embodied in distinctive motifs such as Pisang Agung and Kuda Kencak, is preserved as a unique resource advantage (Sumiati et al., 2024). Beyond cultural heritage, this research highlights the importance of global tools such as digital platforms in facilitating knowledge-sharing and consumer education in international markets (Hu et al., 2024). The utilization of diaspora networks is identified as a key strategy for overcoming the challenges of foreign markets through the leveraging of specific ecosystem advantages (Li et al., 2019). The presence of the diaspora offers strategic advantages due to their deep understanding of both the culture of the home country and the host country (Williams & Dvoulety, 2025). Research findings indicate that the success of market expansion heavily depends on the maturity of network competencies and mutual trust in digital interactions (Augustie et al., 2025; Wziatek-Stasko & Pobiedzinska, 2022). The implementation of open innovation through external collaboration has proven capable of accelerating internationalization efforts while strengthening business resilience (TanTai et al., 2024). The conclusion of this study affirms that the synergy between adaptive local wisdom and smart international support instruments creates a resilient and sustainable business model for SMEs on the global stage